A pragmatics analysis of imperative form and function in Netflix cooking program Nadiya Bakes First Season (2021) - Adik Emil Fransiska; Chusni Hadiati; Usep Muttaqin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
This research aims to identify the forms and functions of imperative utterances produced by Nadiya Hussain in the Netflix cooking show, Nadiya Bakes First Season. The data of this research are imperative utterances produced by Nadiya while delivering her recipes. The descriptive qualitative method and the technique of purposive sampling are applied to answer the research questions. Based on the analysis, there are 310 imperative utterances produced by Nadiya that can be analyzed according to Holmes in Richard and Schmidt’s (1983) theory of imperative form and Condoravdi and Laurer’s (2012) theory of imperative function. The results show that based on the imperative form, base form of verb highly appeared in the show because it has the simplest form and is usually explicit enough to prevent misunderstanding about the cooking instructions. Besides, verb ellipsis has no occurrence due to the help of visualization of Nadiya while delivering the instructions. Based on the imperative functions, commands function dominates in this show due to the effectiveness of the function which is directly expressed from utterances produced by Nadiya. Group IV: disinterest advice and group II: wish-type uses have the least occurrence because these functions do not have the expectation of the realization of imperative from the hearer, while the cooking show aims to get the viewers to follow the instructions given by Nadiya. After reading this research, hopefully, the readers can recognize the forms and functions of imperative utterances, not only employed in the cooking shows but also in their daily communication.